Thermal shock resistance and bonding strength of tri-layer Yb2SiO5/mullite/Si coating on SiCf/SiC composites. Issue 17 (1st December 2020) - Yang, Haitang; Yang, Yanping; Cao, Xueqiang; Huang, Xiaozhong; Li, Yang
Abstract: A Yb2 SiO5 /mullite/Si tri-layer environmental-barrier-coating (EBC) were coated on SiCf /SiC substrates via Air Plasma Spraying (APS). The thermal cycle tests (TCT) were conducted under thermal corrosive condition of vapor-oxygen (50 vol% H2 O and 50 vol% O2 ) with thermal shock from 1200 °C to 200 °C. Microstructures, weight loss and bonding strength of the samples were systemically investigated after 101, 396, 606 and 700 TCT cycles respectively. The results show that the corner of the tri-layer coating peel off from the sample with weight loss of 1.3% after 700 TCT cycles. The bonding strength between substrate and tri-layer coatings gradually decreases to 6.79 MPa (approximately 55.2% of virgin specimens) after 700 cycles due to thermal shock induced cracks distributed horizontally within Si layers and between Si layer and outer layers.